Kajian Dramatism Theory Kenneth Burke: (Potret Pesan Komunikasi Aa Gym) - Kholiq, Abd. (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2015)
Burke's theory compares life to a performance and states that, as in a theatrical work, life requires the existence of an actor, a scene, some tools for the scene, and a goal. This theory allows a rhetorical critic to analyze the speaker's motives by identifying and learning these elements. Furthermore, Burke believes, guilt is the main motive for the speaker, and Dramatism states that a speaker will be most successful when they give their audience a way to erase their guilt.